Evaluation of layback spin in figure skating - Jastšenjski Ksenija; Mandarić Sanja (Fizička Kultura, 2011)
Layback spin is considered as one of the most beautiful and elegant spins performed in figure skating. It is also one of the required spins in competitive short program in female category. Different techniques of executing layback spin with variations in changing the positions of free parts of the body, as well as the evaluation of layback spin in accordance with ISU rules and regulations, which have been used in all International Skating Federation competitions since 2004 (World and European championships, Olympic Games) are presented in this paper. Due to very difficult position of the body while performing a layback spin, it is essential that the skaters who want to master it should have excellent agility (especially of the spinal column and shoulder and knee joints) and balance. Layback spin performance requires significant skating knowledge, so it cannot be performed by beginners. Depending on the fl exibility and creativity, a skater can execute various positions of the head, arms, body and free leg while performing a layback spin. In some cases, these variations can increase the level of difficulty, and in others only the mark given for executing this spin.